Investing in academic staff development to foster transformative learning for sustainable e-learning: A case of one insitution of higher learning - Magunje, C.; Chigona, A.; Gachago, D. (South African Journal of Higher Education, 2024)
The COVID-19 pandemic revealed the central role of academic staff development for e-learning in higher education institutions globally. Most universities in developing countries such as Zimbabwe did not emphasise this, resulting in poor implementation of e-learning as a mode of delivery. While e-learning has since been introduced in most universities in the developing context, technology is mainly used as a substitute for traditional learning approaches, rather than as an innovative mode of curriculum delivery. Using a case study approach and semi-structured interviews, this study sought to explore the trajectory of nine e-learning actors at an African university to determine the role and effectiveness of contextualised academic staff development interventions in e-learning adoption. The findings of the study show that the establishment of academic staff development and the provision of transformative learning-focused training and learning design interventions led to lecturers’ acquisition of e-learning knowledge and skills, including a change in their attitude towards e-learning. To be effective, therefore, academic staff development in developing contexts should provide transformative learning-focused, context-based, continuous training that emphasises relationships with lecturers to ensure sustainable and effective e-learning adoption.